“YUK NABUNG SAHAM” Antara Untung dan Buntung Deteksi Dini dengan ICHIMOKU - Budi Wasito; Brastoro Brastoro; Sigit Birowo (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
Yuk Nabung Saham (YNS) is a campaign to invite the public as potential investors to invest in the capital market by buying stocks regularly and periodically. This campaign is intended to change the habits of the Indonesian people from the habit of saving to investing, so that the Indonesian people begin to move f om a saving society to an investment society. Since the Yuk Nabung Saham campaign was launched on the 12 November 2015 by the Vice President of the Republic of Indonesia Mr. Muhammad Jusuf Kalla, it turned out that the Indonesia Stock Exchange (IDX) was able to encourage an increase in the number of investors including millennial investors. Based on IDX data, the number of single investor identification (SID) at the end of 2020 increased by 1.39 million, a jump of 61% compared to the end of 2019. So that the number of SID increased from 2.4 million to 3.88 million. In fact, as of 4 February 2021, the number of SIDs on the capital market has exceeded 4.1 million. In this regard, people who have chosen the capital market as a medium for saving, however, need to be enlightened about the need for indicators to be used to anticipate whether stock savings will increase or vice versa. Deep downtrend conditions have an impact on the risk of eroding the value of stock deposits so that you must take cut-loss steps as soon as possible so that the losses will deepen. For this reason, the team of lecturers, through community service activities in collaboration with DEKOPINDA, gave a webinar with the title